Strategic water resource management: pump stations in Fayoum City, Egypt - Kotb, Sultan; Cheng, Li; Amin, Mohamed; Elzoghby, Mohamed Monir; Nasr, Ahmed (Frontiers in Water, 2024)
Water scarcity presents significant challenges to sustainable development, particularly in arid regions like Fayoum City, Egypt, which faces particular water challenges due to its unique topography. This study explores the pivotal role of pump stations and wastewater reuse in mitigating water scarcity and promoting sustainable water management practices. Utilizing a comprehensive mixed-method approach, including desk research, field surveys, stakeholder interviews, and integrating the Analytic Hierarchy Process (AHP) into a decision-making framework. The study categorizes pump stations into priority ranking groups based on the evaluation of the following criteria: efficiency, operating hours, working unit ratio, and discharge capacity. The investigation reveals that the 72 pump stations in Fayoum City play a vital role in regulating water levels, optimizing distribution, and facilitating the reuse of irrigation wastewater. Despite operational challenges, such as manpower shortages and maintenance issues, these stations are crucial for sustaining agricultural productivity and addressing water scarcity concerns, including the prevention of recurring inundation events like the one in 2012. Moreover, the study underscores the potential of wastewater reuse as a sustainable solution to water scarcity, particularly in meeting agricultural water demands and mitigating water balance issues, such as inundation. Based on the findings, the study proposes actionable recommendations, including upgrading high-priority pump stations, evaluating lower-priority ones, enhancing canal infrastructure, and promoting water-efficient irrigation methods. In conclusion, this study provides valuable insights into the pivotal role of pump stations and wastewater reuse in addressing water scarcity challenges in arid regions. By implementing the proposed recommendations, Fayoum City can optimize its water management practices, ensure water security, and support the long-term development of the region.